Bilateral cadaveric variations of musculocutaneous nerve and median nerve in the anterior brachium: a case report - Periyasamy, Vinodhini; Kishore, G. Krishna; Ramachandra , Raghavendhra Devanga (International Journal of Research in Medical Sciences, 2024)
Formation of the brachial plexus is by the union of ventral rami of C5-T1 spinal nerves. The musculocutaneous nerve is a continuation of the lateral cord, pierces the coracobrachialis and supplies the flexor compartment of the arm. Our case report presents a unique bilateral cadaveric variation in the musculocutaneous nerve and median nerve branching patterns, in the flexor compartment of the arm. A case report of bilateral variations of musculocutaneous nerve and median nerve (R-Right, L-Left) was found during the routine dissection in the Department of Anatomy, Shridevi Institute of Medical Sciences and Research Hospital, Tumakuru. From the right lateral cord, separation of few nerve fibres forming the lateral root of the median nerve was appreciated. The lateral root joins the medial root of the medial cord, after emerging out of the ulnar nerve and forms the initial segment of median nerve. Before the union of lateral and medial roots of initial segment of median nerve, ulnar nerve, medial cutaneous nerve of arm and medial cutaneous nerve of forearm descends along the medial aspect of the right arm. From the left lateral cord musculocutaneous nerve pierces the coracobrachialis. Before piercing the muscle, it gives one vascular branch and a motor branch. After piercing, the musculocutaneous nerve runs downwards and gives a motor branch to left biceps brachii. Variations of brachial plexus are frequently subjected to compression neuropathy. During surgical approaches to the brachium region, awareness about the anatomical variations of lateral and medial cords is mandatory for diagnosing the peripheral nerve entrapment syndrome. An integrated understanding of these branches prevent iatrogenic injuries during surgical procedures.